Capecitabine and lapatinib uptake in surgically resected brain metastases from metastatic breast cancer patients: a prospective study. Issue 2 (11th July 2014) - Morikawa, Aki; Peereboom, David M.; Thorsheim, Helen R.; Samala, Ramakrishna; Balyan, Rajiv; Murphy, Conleth G.; Lockman, Paul R.; Simmons, Ahkeem; Weil, Robert J.; Tabar, Viviane; Steeg, Patricia S.; Smith, Quentin R.; et al.
Abstract: Background: Breast cancer brain metastases (BCBM) are challenging complications that respond poorly to systemic therapy. The role of the blood–tumor barrier in limiting BCBM drug delivery and efficacy has been debated. Herein, we determined tissue and serum levels of capecitabine, its prodrug metabolites, and lapatinib in women with BCBM resected via medically indicated craniotomy. Methods: Study patients with BCBM requiring surgical resection received either single-dose capecitabine (1250 mg/m 2 ) 2–3 h before surgery or 2–5 doses of lapatinib (1250 mg) daily, the last dose 2–3 h before surgery. Serum samples were collected serially on the day of surgery. Drug concentrations were determined in serum and BCBM using liquid chromatography tandem mass spectrometry. Results: Twelve patients were enrolled: 8 for capecitabine and 4 for lapatinib. Measurable drug levels of capecitabine and metabolites, 5′-deoxy-5-fluorocytidine, 5′-deoxy-5-fluorouridine, and 5-fluorouracil, were detected in all BCBM. The ratio of BCBM to serum was higher for 5-fluorouracil than for capecitabine. As for lapatinib, the median BCBM concentrations ranged from 1.0 to 6.5 µM. A high variability (0.19–9.8) was noted for lapatinib BCBM-to-serum ratio. Conclusions: This is the first study to demonstrate that capecitabine and lapatinib penetrate to a significant though variable degree in human BCBM. Drug delivery to BCBM is variable and in many cases appears partially limiting. Elucidating mechanisms that limit drug concentration and innovative approaches to overcome limited drug uptake will be important to improve clinical efficacy of these agents in the central nervous system. Trial registration ID: NCT00795678.